Terapi Bekam (Hijamah): Tinjauan Literatur dari Perspektif Medis dan Keislaman - Abul A’la Al Maududi; Endah Khamelia; Yuni Purwanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Cupping therapy is a traditional therapeutic method that has long been recognized in Thibbun Nabawi and continues to be used as a complementary therapy in contemporary healthcare. Along with the development of scientific research, cupping therapy has increasingly been examined from a medical perspective, highlighting the need for an integrative review that combines medical evidence and Islamic perspectives. This study aims to examine cupping therapy from both medical and Islamic perspectives based on a literature review. This study employed a qualitative approach using a literature review design. Data were collected from national and international scientific articles published between 2019 and 2025 through indexed databases, including Scopus, PubMed, Google Scholar, and Garuda. The review was complemented by Islamic sources such as the Qur’an, Hadith, and scholarly works on Thibbun Nabawi. Data were analyzed using descriptive qualitative analysis by categorizing findings into medical benefits and religious foundations of cupping therapy. The literature review indicates that cupping therapy has potential medical benefits, including pain reduction, blood pressure control, and improvement of metabolic parameters such as blood glucose and cholesterol levels. From an Islamic perspective, cupping therapy is regarded as part of Thibbun Nabawi and is recommended as a form of human effort to maintain health, while ultimate healing is believed to come from Allah SWT. Cupping therapy demonstrates strong relevance from both medical and religious perspectives. Integrating cupping therapy with modern medical principles and Islamic values may provide a holistic health approach that supports promotive, preventive, and curative healthcare services within complementary medicine.